Virulence factor RNA transcript expression in the Leishmania Viannia subgenus: influence of species, isolate source, and Leishmania RNA virus-1 - Kariyawasam, Ruwandi (Trop Med Health, 2019)
BACKGROUND: Leishmania RNA virus-1 (LRV1) is a double-stranded RNA virus identified in 20–25% of Viannia—species endemic to Latin America, and is believed to accelerate cutaneous to mucosal leishmaniasis over time. Our objective was to quantify known virulence factor (VF) RNA transcript expression according to LRV1 status, causative species, and isolate source. METHODS: Eight cultured isolates of Leishmania were used, four of which were LRV1-positive (Leishmania Viannia braziliensis [n = 1], L. (V.) guyanensis [n = 1], L. (V.) panamensis [n = 2]), and four were LRV1-negative (L. (V.) panamensis [n = 3], L. (V.) braziliensis [n = 1]). Promastigotes were inoculated into macrophage cultures, and harvested at 24 and 48 h. RNA transcript expression of hsp23, hsp70, hsp90, hsp100, mpi, cpb, and gp63 were quantified by qPCR. RESULTS: RNA transcript expression of hsp100 (p = 0.012), cpb (p = 0.016), and mpi (p = 0.022) showed significant increases from baseline pure culture expression to 24- and 48-h post-macrophage infection, whereas hsp70 (p = 0.004) was significantly decreased. A trend toward increased transcript expression of hsp100 at baseline in isolates of L. (V.) panamensis was noted. Pooled VF RNA transcript expression by L. (V.) panamensis isolates was lower than that of L. (V.) braziliensis and L. (V.) guyananesis at 24 h (p = 0.03). VF RNA transcript expression did not differ by LRV1 status, or source of cultured isolate at baseline, 24, or 48 h; however, a trend toward increased VF RNA transcript expression of 2.71- and 1.93-fold change of mpi (p = 0.11) and hsp90 (p = 0.11), respectively, in LRV1 negative isolates was noted. Similarly, a trend toward lower levels of overall VF RNA transcript expression in clinical isolates (1.15-fold change) compared to ATCC® strains at 24 h was noted (p = 0.07). CONCLUSIONS: Our findings suggest that known VF RNA transcript expression may be affected by the process of macrophage infection. We were unable to demonstrate definitively that LRV-1 presence affected VF RNA transcript expression in the species and isolates studied. L. (V.) guyanensis and L. (V.) braziliensis demonstrated higher pooled VF RNA transcript expression than L. (V.) panamensis; however, further analyses of protein expression to corroborate this finding are warranted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s41182-019-0153-x) contains supplementary material, which is available to authorized users.